Induksi Akar pada Eksplan Tunas Anggrek Grammatophylum scriptum var. citrinum secara In Vitro pada Media MS dengan Penambahan NAA Dan BAP - Mayta Novaliza Isda; Siti Fatonah (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2014)
Grammatophyllum scriptum var. citrinum is one variant of endangered from habitat destruction due to logging and forest fires and hunts by orchid collectors. The aim of this study was to determine the effect of BAP and NAA concentration in the root orchid propagation G. scriptum var. citrinum. The results showed that the application of BAP and NAA significant effect on the time of formation appeared roots (19 days), the best root number in the treatment of BAP 0.5 mg/l + 1.0 mg/l NAA for (5 pieces) and root length was obtained NAA 1 mg/l and a combination of 1.0 mg/l BAP + 0.5 mg/l NAA respectively 6.66 cm and 7.40 cm.